Music, education, and multiculturalism : foundations and principles - Volk, Terese M., 1948-; Oxford University Press (New York : Oxford University Press, 1998)
In today's multi-ethnic classroom, multiculturalism plays an increasingly vital role. What it is, how it developed, and what it means for education, especially music education, is the essence of this three-part book. Music, Education, And Multiculturalism traces the growth and development of multicultural music education in the United States from its start in the early 1900s to the present, and describes the state of multicultural music education internationally. Designed to assist music educators at all levels in understanding and implementing multicultural education, this book provides suggestions for curricular development, offers teaching strategies, and provides practical applications including materials and methodologies. Combining personal narrative and oral history with the support of primary and archival documents, this text is essential reading for all students and teachers of the history and foundations of music education and of multiculturalism in general education.
The philisophical debate -- The difficult question of multiculturalism -- The historical perspective -- Prelude to the twentieth century -- The first steps 1900-1928 -- The international movement 1929-1953 -- Oivotal changes 1954-1967 -- Multicultural awareness 1968-1990 -- Since 1990 -- Interlude : the end of the beginning -- Multiculturalism in interantional music education -- Implications for music education -- Music teacher education -- Materials and methodologies -- Final considerations : problems and possibilities.
Includes bibliographical references (pages 205-257) and index.
Keywords: Music -- Instruction and study -- United States; Multicultural education